Adversarial proceedings before the African Court on Human and Peoples’ Rights (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
As a universal principle, adversarial proceedings are implemented by all international human rights courts. The African Court on Human and Peoples’ Rights is no exception, as adversarial proceedings are also enshrined in article 7(1)(c) of theAfrican Charter on Human and Peoples’ Rights and in article 26 of the Protocol establishing the Court. However, the universal formal enshrinement of adversarial proceedings does not guarantee uniformity in its implementation. The purpose of this article is to demonstrate, through exegetical and casuistic methods, that despite the laconic formulation of the adversarial principle in the African Charter on Human and Peoples’ Rights, the Court is consolidating this principle. In the African legal system, the particularity of adversarial proceedings is more perceptible when viewed in the light of the jurisprudence of the African Court. An examination of the Court’s case law reveals that adversarial proceedings are an established principle before the African human and peoples’ rights tribunal.